The criminal liability of night terror in Malaysia - Mohamad Yunus, Mohamad Ismail (Thomson Reuters, 2018)
Brian Thomas has been charged with murdering his wife, Christine Thomas. He admitted killing his wife however he blames it on his rare sleep disorder. Earlier that fateful evening, a group of youths made them feel uncomfortable and they decided to move and park somewhere else for the night. While sleeping, Mr Thomas believed that the youths had broken into his caravan. He thought he was fighting them off when in fact he was strangling his wife. The High Court judge, Davis J., held that in the eyes of the law the accused has no criminal liability for what had happened. Thus, if this scenario happens in Malaysia due to the sleep disorder specifically “night terror”, does the Malaysian Penal Code provide an adequate defense that can be invoked by the accused person?